Enhanced mechanical properties for 304L stainless steel parts fabricated by laser-foil-printing additive manufacturing. (September 2019) - Hung, Chia-Hung; Sutton, Austin; Li, Yingqi; Shen, Yiyu; Tsai, Hai-Lung; Leu, Ming C.
Abstract: In this study we demonstrate that the mechanical properties of 304L stainless steel (304L SS) parts fabricated by the laser-foil-printing (LFP) additive manufacturing process can be enhanced as compared to parts fabricated by the selective laser melting (SLM) technology. The tensile test results indicate that the LFP fabricated parts achieve ˜15% and ˜10% higher in yield strength and ultimate tensile strength, respectively, compared to the SLM fabricated parts. This is mainly because the use of foil feedstock in LFP leads to a higher cooling rate during the solidification of molten metal than the use of powder bed in SLM, due to higher thermal conductivity in foils than powders. By using electron backscattered diffraction it is confirmed that the LFP parts have finer grain structures than the SLM parts, implying a higher cooling rate in LFP. The LFP process also produces metal parts with an average oxygen content about 75% less than those by the SLM process, due to ˜10 times of surface area per unit volume in powders than foils.